2007
DOI: 10.1002/ejlt.200600219
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic profiles of lipid classes, fatty acids and triacylglycerol molecular species of peas (Pisum sativum L.)

Abstract: Seed oils from four legume cultivars of Pisum sativum, grown in Japan, were extracted and classified by thin-layer chromatography (TLC) into seven fractions: hydrocarbons (HC; 0.5-0.9 wt-%), steryl esters (SE; 0.8-2.4 wt-%), triacylglycerols (TAG; 31.2-40.3 wt-%), free fatty acids (FFA; 1.3-2.7 wt-%), 1,3-diacylglycerols (1,3-DAG; 1.0-1.8 wt-%), 1,2-diacylglycerols (1,2-DAG; 1.0-2.2 wt-%) and phospholipids (PL; 52.2-61.3 wt-%). All lipid samples had high amounts of total unsaturated fatty acids, representing 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…There were no significant differences (P [ 0.05) in the lipid components among the four cultivars. However, the amounts of TAG were higher in the broad beans than in peas reported previously [21].…”
Section: Lipid Components In the Beanscontrasting
confidence: 49%
See 2 more Smart Citations
“…There were no significant differences (P [ 0.05) in the lipid components among the four cultivars. However, the amounts of TAG were higher in the broad beans than in peas reported previously [21].…”
Section: Lipid Components In the Beanscontrasting
confidence: 49%
“…However, the percentage of stearic (18:0) acid was almost the same value between the TAG and PL. These FA profiles are not similar to the results observed in typical vegetable seeds such as peas [21] or kidney beans [22]. The oils from legumes could be a potential source of tocopherols (unpublished work).…”
Section: Fa Composition Of Tag and Plmentioning
confidence: 77%
See 1 more Smart Citation
“…When choosing varieties for cultivation, it is important to consider their susceptibility to plant nutrient uptake and soil properties, climate adaptive capacity, and other agronomic features relevant to the growing region. Results obtained in this study were also comparable to the findings of other authors (Wang and Daun, 2004;Yoshida et al, 2007;Harmankaya et al, 2009).…”
Section: Resultssupporting
confidence: 93%
“…In addition, due to its high ability to fix nitrogen, pea could be efficiently used as a biodiesel resource to replace canola oil and other oilseed crops that require high costs for use in biodiesel production [ 2 ]. With respect to productivity, pea ranks fourth worldwide after soybean, peanut, and dry bean [ 3 ]. Although pea germplasm is rich in genetic diversity, a few research studies have been conducted and have shown a low oil content in peas varying between 1.5% and 3.7% [ 3 , 4 , 5 ], indicating that the currently available cultivars have a limited oil content.…”
Section: Introductionmentioning
confidence: 99%